Stress beyond coping? A Rasch analysis of the Perceived Stress Scale (PSS-14) in an Aboriginal population. - Pedro Henrique Ribeiro Santiago; Rachel Roberts; Lisa Gaye Smithers; Lisa Jamieson (PLoS ONE)
The history of colonization contributed to Aboriginal and Torres Strait Islanders becoming one of the most disadvantaged groups in Australia. The multiple social inequalities, and therefore the constant insecurities for many about low income, poor living conditions, unemployment, and discrimination, generate chronic stress in this population. In the Baby Teeth Talk Study, an oral-health randomized controlled trial, the Perceived Stress Scale (PSS-14) was administered to 367 pregnant Aboriginal women at baseline. The aim of the present study was to evaluate the validity and reliability of the PSS-14 in an Aboriginal population. The study analysed: (a) model fit; (b) dimensionality; (c) local dependence; (d) differential item functioning; (e) threshold ordering and item fit; (f) targeting; (g) reliability; and (h) criterion validity. The dimensionality analysis indicated a two-factor structure, with negatively and positively worded items clustering together and 21.7% (95% Agresti-Coull C.I. [17.8%, 26.2%]) statistically significant t-tests between the persons' estimates. After the creation of composite items, the revised Perceived Distress (χ2 (21) = 11.74, p = 0.946) and Perceived Coping (χ2 (28) = 17.63, p = 0.935) subscales fitted the Rasch model. Reliability was modest (PersonSeparationIndexdistress = 0.72; PersonSeparationIndexcoping = 0.76). The latent correlation between the Perceived Distress and Perceived Coping subscales was r = 0.14. It is hypothesized that the social inequalities experienced by the Aboriginal population are so pronounced that even Aboriginal pregnant women that perceived themselves as coping well with life challenges ended up endorsing items regarding high levels of stress. The present research showed that a revised PSS-14 is a culturally valid and modestly reliable psychological instrument to measure stress in a population of pregnant Aboriginal women in Australia.